PENGARUH DUKUNGAN KADER KESEHATAN MELALUI MEDIA GRUP WHATSAPP TERHADAP KEPATUHAN MINUM OBAT PADA PASIEN TBC PARU - Yudha Laga Hadi Kusuma; Siti Mahnunah; Fitria Wahyu Ariyanti (MEDICA MAJAPAHIT, 2025)
Compliance with taking medication is still a problem for pulmonary TB patients even though a medication supervisors (PMO) has been appointed to make treatment successful and prevent TB transmission in the community. Non-compliance with treatment will cause a high rate of treatment failure in pulmonary TB patients and the incidence of drug resistance. This study aims to determine the Influence of Health Cadre Support as Medication Supervisors (PMO) through WhatsApp Group Media on Medication Compliance in Pulmonary Patients in the UPTD Puskesmas Pungging Area.This research uses a research design pre-experiment one group pretest-posttest. The population in this study was 40 respondents. The sample in this study consisted of 15 respondents, who are taken using tsimple random sampling echniques. The instrument used was the MMAS-8 questionnaire to measure medication adherence. Statistical test using Wilcoxon sign rank test. The research results show that the average score of adherence to taking medication in pulmonary TB patients before intervention was given in the UPTD Puskesmas Pungging area was 5.47 in the low compliance category. Meanwhile, the average score of adherence to taking medication in pulmonary TB patients after being given intervention in the UPTD Puskesmas Pungging area was 7.47 in the moderate compliance category.Statistical test results show significance value (p) 0.001 which means that there is an influence of support from health cadres as medication supervisors (PMO) through WhatsApp group media on medication compliance in pulmonary TB patients in the UPTD Puskesmas Pungging area. The test results also show mark positive rank 15, which means that all respondents (100%) experienced an increase in compliance scores (positive ranks 15). Based on the results of this study, it is expected that the UPTD Puskesmas Punggig area can continue to implement PMO in the WhatsApp group which aims to monitor OAT consumption in pulmonary TB patients. In addition, a WhatsApp group can be formed within the patient's family members to help supervise the patient's medication consumption.